Phospholipid in the hexagonal II phase is immunogenic: evidence for immunorecognition of nonbilayer lipid phases in vivo. - Rauch, J (1990)
Immunization of mice with phosphatidylethanolamine in the hexagonal II phase but not the bilayer phase resulted in the induction of anti-phospholipid antibodies. These antibodies, which were strongly reactive with phosphatidylethanolamine and crossreactive with cardiolipin, had functional lupus anticoagulant activity and were characteristic of autoantibodies common in patients with autoimmune disease. Recognition of the hexagonal II phase by the afferent limb of the immune system suggests that nonbilayer phospholipids can arise in the course of membrane remodeling and induce the autoantibodies of disease.